Increasing Critical Thinking Skills Through Natural Science Learning Based on the Integration of Guided Inquiry with Numbered Heads Together - Alaniyah Syafaren; Yustina Yustina; Imam Mahadi; Rian Vebrianto (Journal of Educational Sciences, 2019)
Process of science learning stresses on giving students direct experience to develop their competence. Therefore, teachers are required to be creative and innovative to improve students’ critical thinking. Accordingly, there is a need for a research on “The science learning based on guided inquiry integration with Numbered Heads Together (NHT) toward critical thinking skill”. This research aim to figure out of influence of the science learning based on guided inquiry integration with NHT. This research is a quasi-experimental study, with design "non-equivalent group control design". This research was conducted at September-December 2018 with samples of the experimental class (n = 40) and the control class (n = 40) at class VIII SMP N 21 Pekanbaru. The research instrument consisted of questions to test students' critical thinking skills. This shows the research instrument at a good and quality stage. The results of this study note that there are significant differences in the average value of the Post test students' critical thinking skills between the experimental class amounted to 75.00 with the control class 67.00 after the intervention (P <0.05). So that the use of Integration of guided inquiry with NHT in the learning process can improve students' critical thinking skills.